The Analysis Maturity level of the Government's Internal Control and Sustainable Development Goals in Kudus: Analysis Maturity level of the Government's Internal Control and Sustainable Development Goals in Kudus - Wahyu Tirta; Bonnix; Anisya (International Economic Conference of Business and Accounting, 2024)
This study aims to analyze the maturity level of the government's internal control system by the Inspectorate of Kudus in realizing regional financial transparency and accountability, by integrating the theme of Sustainable Development Goals (SDGs) and the concept of green economy. The research method used is descriptive qualitative, the research informants consist of Kudus Inspectorate officials and auditors. The results showed that the maturity level of the internal control system at the Inspectorate of Kudus was at the defined level. Internal controls implemented contribute significantly to improving transparency and accountability of local finances, in line with SDG's goals, especially SDG 16 (Peace, Justice, and Strong Institutions) In addition, the application of the green economy concept is reflected in budget management that supports sustainability and resource efficiency. However, this study found challenges in implementing the internal control system, less understanding of internal control among employees, and coordination with other Government Internal Audit agencies.